Boron Nanowheels with Axles Containing Noble Gas Atoms: Viable Noble Gas Bound M©B10− Clusters (M=Nb, Ta). Issue 14 (12th February 2018) - Pan, Sudip; Kar, Susmita; Saha, Ranajit; Osorio, Edison; Zarate, Ximena; Zhao, Lili; Merino, Gabriel; Chattaraj, Pratim K.
Abstract: The viability of noble gas axled boron nanowheels Ng n M©B10 − (Ng=Ar–Rn; M=Nb, Ta; n =1, 2) is explored by ab initio computations. In the resulting Ng2 –M complexes, the Ng‐M‐Ng nanorod passes through the center of the B10 − ring, providing them with an inverse sandwich‐like structure. While in the singly Ng bound analogue, the Ng binding enthalpy H b at 298 K ranges from 2.5 to 10.6 kcal mol −1, in doubly Ng bound cases it becomes very low for the Ng2 M©B10 − →Ng+NgM©B10 − dissociation channel, except for the case of Rn, for which the corresponding H b values are 3.4 (Nb) and 4.0 kcal mol −1 (Ta). For a given Ng, Ta has slightly higher Ng‐binding ability than Nb. The corresponding free‐energy changes indicate that these systems, particularly the Xe and Rn complexes, are good candidates for experimental realization in a low‐temperature matrix. The Ng−M bonds were found to be covalent in nature, as reflected in their large Wiberg bond indices, formation of a 2c–2e σ orbital between Ng and M centers in natural bond orbital and adaptive natural density partitioning (AdNDP) analyses, and the short Ng−M distances. Energy decomposition analysis and a study on the natural orbitals for chemical valence show that the Ng−M contact is supported mainly by the orbital and electrostatic interactions, with almost equal contributions. Although both the Ng→M σ donation and Ng←M π backdonation play roles in the origin of orbital interaction, the former is significantly dominant over the latter. Further, AdNDP analysis indicates that the doubly aromatic character (both σ and π) in MB10 − clusters is not perturbed by the interaction with Ng atoms. Abstract : Wheel gets an axle : With preservation of the wheel geometry of the M©B10 − (M=Nb, Ta) moiety, two axles containing noble gas (Ng) atoms were installed on both sides. The resulting Ng2 M©B10 − complexes, which were studied by ab initio calculations, have an inverse sandwich‐like structure in which the covalently bound Ng‐M‐Ng nanorod passes through the center of the B10 ring (see figure).